Hydrogen-rich syngas production from bi-reforming of greenhouse gases over zirconia modified Ni/MgO catalyst - Farooqi, A.S. (John Wiley and Sons Ltd, 2022)
Bi-reforming of methane (BRM) is gaining an increase interest due to the critical requirements to mitigate global warming and provide alternative energy resources. However, there has been a serious challenge to the scale-up of the process to commercial production due to the catalyst deactivation. In the present study, the influence of ZrO2 modifications on the activity and stability of MgO-supported Ni catalyst in the BRM reaction was investigated. The ZrO2-MgO mixed oxide support was prepared by co-precipitation method with variation in the ZrO2 composition and subsequently impregnated with Ni. The characterization of the freshly prepared Ni/MgO and Ni/MgO-ZrO2 catalysts using N2 physisorption analysis, X-Ray Diffraction (XRD), FESEM, XPS, H2-TPR, and CO2-TPD techniques revealed suitable physicochemical properties for the BRM reaction. The Ni/MgO-ZrO2 catalysts showed an improved performance in the BRM reaction in terms of activity and stability compared to the Ni/MgO at 800Â°C and CH4, H2O, CO2 ratio of 3:2:1, respectively. The best performance was obtained using the Ni/15ZrO2-MgO for the BRM with CO2 and CH4 conversion of 81.5 and 82.5, respectively. The characterization of the spent Ni/MgO catalyst using Raman spectroscopy, FESEM, and High Resolution Transmission Electron Microscopy (HRTEM) analysis revealed the formation of amorphous carbon that could be responsible for its fast deactivation. Â© 2021 John Wiley & Sons Ltd.